Kazakhstan : Enhancing the Fiscal Framework to Support Economic Transformation - World Bank (World Bank, Washington, DC, 2017)
Kazakhstan benefited from the oil boom of 2000–14 that led to income growth and poverty reduction and helped build a fiscal cushion to stabilize the economy during downturns. During this period, nominal GDP per capita increased ten-fold, from US$1,229 in 2000 to US$12,807 in 2014, mainly due to price effects from currency appreciation that followed an expansion of the oil sector. Income growth led to a substantial decline in the poverty rate, from 77 percent in 2001 to 16 percent in 2014. As oil output more than doubled and the oil price super-cycle emerged, the Government of Kazakhstan (GoK) accumulated substantial fiscal savings in its oil fund, the National Fund of the Republic of Kazakhstan (NFRK).2 Fiscal savings in the NFRK peaked at US$73 billion (33 percent of GDP) at end-2014. A portion of these funds was used for anti-crisis programs in 2007-10, during which time the fiscal stimulus program totaled US$18 billion (about 15 percent of GDP). The authorities must urgently adopt and start implementing a fiscal consolidation strategy and refocus macro-fiscal policy on promoting diversified growth and high-quality job creation. The countercyclical fiscal stance adopted in 2014 led to an increase in the nonoil fiscal deficit (NOD), which is too high to ensure medium-term fiscal sustainability and threatens the long-term growth potential of the nonoil tradable economy. Successful fiscal consolidation would require: (i) reducing inefficient expenditure that distorts private incentives while redirecting savings toward productivity-enhancing spending; and (ii) eliminating inefficient tax benefits that result in an uneven playing field for investment. While pursuing a fiscal consolidation effort over the medium term, there are potential benefits to reviewing Kazakhstan’s fiscal policy framework and institutions with the goal of strengthening their coherence, credibility, and flexibility. This Public Finance Review (PFR) aims to help the authorities identify areas for fiscal consolidation that will bring about fiscal sustainability in the medium term and support economic transformation in the long run. While developing a fiscal consolidation strategy, the authorities should address four policy areas to enhance fiscal sustainability and support economic transformation. These are discussed in the following four policy focus chapters: (i) enhancing the credibility of the fiscal policy framework; (ii) improving public spending efficiency and effectiveness; (iii) mobilizing nonoil revenue and optimizing the tax system; and (iv) strengthening fiscal policy institutions.